Odsun sovětských vojsk z Československa 1989 - 1991 : dokumenty - Pecka, Jindřich (Studie, materiály, dokumenty, 1996)
Engl. Zsfassung u.d.T.: The withdrawal of the Soviet armed forces from Czechoslovakia, 1989-1991 . documents